PERANCANGAN PLTS ATAP PADA GEDUNG KANTOR BUPATI TAPANULI UTARA DENGAN ARSITEKTUR RUMAH ADAT BATAK TOBA - Octopianus Silaban, Irwan; Satya Kumara, I Nyoman; Setiawan, I Nyoman (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUM, 2021)
Solar Power Plant (PLTS) is a technology to convert solar energy into electricity. RUEN states that the potential for solar electricity in Indonesia is estimated at 207.89 GW and it has been determined that the national PLTS capacity target in 2025 is 6.5 GW and continues to increase to 45 GW in 2050. One of the efforts that can be made to achieve this target is to use government buildings as a place to install PLTS. This study was conducted to find out how much potential electrical energy is generated on the rooftop PLTS of the North Tapanuli Regent's office which has a roof slope of 52.70. It was found that the PLTS of the North Tapanuli Regent's office has the potential to generate 39.6 kWp of electrical power. The simulation shows the energy data produced by the PV system is 45,646 kWh in one year and has a role in supplying electrical energy up to 52.9%. So the total of the PV system with Grid electrical energy supplied to the load is 86,233 kWh/year.